Democracy and Its Discontents - Cooper, Karyn. author. aut Link
XVIII, 216 p.
Keywords: This volume brings together important voices regarding constraints and potential possibilities for democracy in action. The book addresses various understandings of democracy and provides specific critiques. Connections between critique, critical literacy, and its potential for society and education are presented and organized smoothly and accessibly, facilitating easy engagement with the ideas within. These ideas have been carefully thought through so that the text becomes accessible, comprehensible and logical. Readers may benefit from this work through its synthetic, international and comparative approach to issues surrounding critical literacy and its relationship with the democratic process. Complementing the text with audio-visual content allows readers to engage with some of the foremost professionals in the field of critical literacy. Videos of Noam Chomsky add to this a definitive view of democratic practice. The authors have striven to make this “video-text” appropriate,interesting and innovative. Moreover, readers may particularly appreciate the informative summary at the end of every chapter, which is presented in more accessible terms for the uninitiated who may be interested in ways of dealing with critical literacy practices in social, political and educational contexts. This is a very personal book that surprises, represents a unique view of the interrelationship between democracy and literacy, reinterprets significant academic writings in critical pedagogy, offers an analysis of theoretical and empirical research, and provides in-depth narratives and portraits of stimulating scholars in education who have worked towards development of an engaged and empowered electorate. .